Determinação do valor da heptoglobina sérica para diagnóstico de hemólise na síndrome HELLP - Menegazzo, Ana Barbara Bordignon Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Context: HELLP syndrome is a severe complication of pre-eclampsia, caracterized by hemolysis, elevated liver enzymes and low platelet count. Although there are standardized laboratory values that define the HELLP syndrome, the difficulty still exists for the characterization of hemolysis. PURPOSE: to evaluate the haptoglobin value to diagnose the hemolysis in HELLP syndrome. METHODS: transversal and prospective study of pregnant and postdelivery women with pre-eclampsia. Laboratory tests evaluated: serum haptoglobin. ROC curve to determine the cutoff value of haptoglobin in the diagnosis of hemolysis in HELLP syndrome. RESULTS: The haptoglobin value for hemolysis diagnosis in HELLP syndrome was 0.26 g / L. DISCUSSION: The best correlation was with haptoglobin and DHL, indicating that this is the best marker of intravascular hemolysis for the diagnosis of HELLP syndrome. CONCLUSION: Serum haptoglobin in cases of pre-eclampsia should be part of routine tests for diagnosis of intravascular hemolysis in HELLP syndrome

Introdução: A síndrome HELLP é uma complicação severa da pré-eclâmpsia, caracterizada por hemólise, elevação das enzimas hepáticas e trombocitopenia. Apesar de haver padronização dos valores laboratoriais que definem a síndrome HELLP, ainda existe dificuldade para a caracterização da hemólise. OBJETIVO: Avaliar o valor de haptoglobina que determina a hemólise nas pacientes com síndrome HELLP. MÉTODOS: estudo transversal e prospectivo de gestantes e puérperas com de pré-eclâmpsia. Exame laboratorial avaliado: dosagem sérica de haptoglobina. Construção da curva ROC para determinar o valor de corte da haptoglobina para diagnóstico de hemólise na síndrome HELLP. RESULTADOS: O valor da haptoglobina para diagnóstico de hemólise em pacientes com síndrome HELLP foi de 0,26g/L. DISCUSSÃO: A melhor correlação observada foi a haptoglobina com a DHL, indicando que este é o melhor marcador de hemólise intravascular para o diagnóstico da síndrome HELLP. CONCLUSÃO: A dosagem sérica da haptoglobina nos casos de pré-eclâmpsia deve fazer parte dos exames de rotina para diagnóstico de hemólise intravascular da síndrome HELLP
Keywords: Mulheres grávidas; Síndrome HELLP; Pre-eclampsia; Heptoglobinas; Hemolise e hemolisinas; Estudos transversais; Hemolysis and hemolysins